Muscular Strength, Power, and Endurance Adaptations after Two Different University Fitness Classes - Brittany S. Hollerbach; Sarah J. Cosgrove; Justin A. DeBlauw; Nattinee Jitnarin; Walker S. C. Poston; Katie M. Heinrich (MDPI AG, 2021)
Physical activity (PA) classes help college students add weekly PA, which can help improve health and maintain body weight. Traditional weight training (TWT) can improve strength and aerobic capacity. High-intensity functional training such as CrossFit® (CF) provides time-efficient workouts with both muscle strengthening and aerobic exercises. Limited research has compared these classes for college students. We examined changes in muscular strength, power, and endurance as well as body composition. Participants were 85 healthy college students enrolled in TWT (n = 36, age 22.6 ± 4.1 years, 72.2% male) or CF (n = 49, age 21.8 ± 3.2 years, 55.1% male) classes meeting twice/wk for 8 weeks between October 2017 and May 2018. Baseline and posttest measurements included a vertical jump, grip strength, a 2 min push-up test, a 1 min squat test, height, weight, and a bioelectrical impedance analysis. Although no significant group × time interactions were found, there was a significant main effect of time for push-ups and squats (both p < 0.001). Participants enjoyed the classes and most planned to continue. Both classes improved muscular endurance although no significant differences were found between them. Activity classes provide college students with an option for increasing their weekly PA and help maintain body composition. Future research should examine the benefits from longer or more frequent classes.